2020
DOI: 10.3171/2018.10.jns181015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel rat model of X-linked hydrocephalus by CRISPR-mediated mutation in L1cam

Abstract: OBJECTIVEEmergence of CRISPR/Cas9 genome editing provides a robust method for gene targeting in a variety of cell types, including fertilized rat embryos. The authors used this method to generate a transgenic rat L1cam knockout model of X-linked hydrocephalus (XLH) with human genetic etiology. The object of this study was to use diffusion tensor imaging (DTI) in studying perivascular white matter tract injury in the rat model and to characterize its pathological definition in histology.METHODSTwo guide RNAs de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…To investigate the epistatic interactions between known hydrocephalus-causing gene mutations, we crossed the Ccdc39 prh allele with the L1cam − allele that we generated recently (Emmert et al, 2019). L1cam y/− single mutant rats show delayed growth and develop mild enlargement of the fourth and lateral ventricles by 3 and 6 weeks postnatally, respectively (Emmert et al, 2019), modeling a mild form of XLH.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To investigate the epistatic interactions between known hydrocephalus-causing gene mutations, we crossed the Ccdc39 prh allele with the L1cam − allele that we generated recently (Emmert et al, 2019). L1cam y/− single mutant rats show delayed growth and develop mild enlargement of the fourth and lateral ventricles by 3 and 6 weeks postnatally, respectively (Emmert et al, 2019), modeling a mild form of XLH.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the epistatic interactions between known hydrocephalus-causing gene mutations, we crossed the Ccdc39 prh allele with the L1cam − allele that we generated recently (Emmert et al, 2019). L1cam y/− single mutant rats show delayed growth and develop mild enlargement of the fourth and lateral ventricles by 3 and 6 weeks postnatally, respectively (Emmert et al, 2019), modeling a mild form of XLH. Survival rate and body weight analyses of male and female postnatal wild-type, L1cam heterozygous/ Ccdc39 heterozygous ( L1cam wt/− ;Ccdc39 wt/prh ), L1cam mutant/ Ccdc39 heterozygous ( L1cam y/− ;Ccdc39 wt/prh ), double-mutant ( L1cam y/− ;Ccdc39 prh/prh ), and L1cam heterozygous/ Ccdc39 mutant ( L1cam wt/− ;Ccdc39 prh/prh ) rats revealed that the stunted growth and premature mortality of Ccdc39 prh/prh rats were exaggerated in the presence of the L1cam -null allele, as evidenced by the decreased survival and growth of male L1cam y/− ;Ccdc39 prh/prh rats ( n =6 and n =2, respectively; P< 0.001 between wild-type and L1cam y/− ;Ccdc39 prh/prh and P< 0.01 between Ccdc39 prh/prh and L1cam y/− ;Ccdc39 prh/prh for survival; P< 0.05 between Ccdc39 prh/prh and L1cam y/− ;Ccdc39 prh/prh for body weight) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations